EDUKASI KESEHATAN PERILAKU GIZI YANG SEHAT PADA SISWI DI MI AL-ISHLAH BANDUNG - Asysyifa Riana; Kiki Kristiandi; Elly Musa; Astrid Astheria Malaihollo; Berlina Saragih; Debora Simamora (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Community service performed at Immanuel Bandung School of Health Sciences aims to see the relationship of nutritional status and nutritional behavior to female students in MI AL-ISHLAH BANDUNG. Research design of this study was cross-sectional study. Sampling method was purposive sampling and number of subject mere 145 students of 3, 4, 5, and 6 done by purposive sampling with 145 samples of students taken from grade 3, 4, 5 and 6 grade in MI AL-ISHLAH BANDUNG. The assessment is done by using questionnaires pre and post test treatment. The results obtained from community service that is the nutritional status of female students in MI AL-ISHLAH with normal category (-2SD to 1SD), while for the nutrition behavior of female students in MI AL-ISHLAH BANDUNG included in the category less (<60%) . Based on the calculation by using T-test obtained results that are not significant (p-value> 0.05), this is due to lack of motivation in applying nutritional behavior